# Solve: x^{2} + 4x - 12 = 0

x = 2, x = -6

x = -2, x = -6

x = 3, x = -4

x = -3, x = 4

**Solution:**

Let us factorise the polynomial to find the value of x by splitting the middle term.

**Step 1: **

Identify the values of a, b and c.

In the above equation, a is coefficient of x^{2 }= 1, b is the coefficient of x = 4 and c is the constant term = - 12.

**Step 2: **

Multiply a and c and find the factors that add up to b.

1 × (- 12) = - 12

⇒ 6 and - 2 are the factors that add up to b.

**Step 3: **

Split bx into two terms.

x^{2} + 6x - 2x - 12 = 0

**Step 4: **

Take out the common factors by grouping.

x(x + 6) - 2(x + 6) = 0

(x - 2) (x + 6) = 0

By putting the factors equal to zero we get two values of x

x - 2 = 0 and x + 6 = 0

x = 2 and x = -6

Thus, the two values that satisfy the equation are 2 and - 6.

## Solve: x^{2} + 4x - 12 = 0

**Summary:**

The values of x for the equation x^{2} + 4x - 12 = 0 is x = 2, -6 which satisfies the equation.

visual curriculum